Self-reported sleep relates to hippocampal atrophy over the adult lifespan – results from the Lifebrain consortium - Fjell, AM; Sørensen, Ø; Amlien, IK; Bartrés-Faz, D; Bros, DM; Buchmann, N; Demuth, I; Drevon, CA; Düzel, S; Ebmeier, KP; Idland, A-V; Kietzmann, TC; et al. (Oxford University Press, 2019)
Objectives Poor sleep is associated with multiple age-related neurodegenerative and neuropsychiatric conditions. The hippocampus plays a special role in sleep and sleep-dependent cognition, and accelerated hippocampal atrophy is typically seen with higher age. Hence, it is critical to establish how the relationship between sleep and hippocampal volume loss unfolds across the adult lifespan.